1997
DOI: 10.21273/jashs.122.6.758
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotics and Exposure to an Acidified Medium on the Elimination of Agrobacterium tumefaciens from Apple Leaf Explants and on Shoot Regeneration

Abstract: A range of antibiotics and short-term exposure to an acidified (pH 3.0) medium were evaluated for their effects on eliminating Agrobacterium tumefaciens, supervirulent strain EHA101 (pEHA101/pGT100), from leaf explants of `Royal Gala' apple (Malus ×domestica Borkh.) and on shoot regeneration. Exposure of leaf explants to regeneration and elongation media containing 100 μg·mL-1 concentrations of the antibiotics carbenicillin (crb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The higher quantity of proliferating cells per explant probably increased the transformation efficiency; however, bacterial overgrowth increased as well (52.1% clusters contaminated compared with 11.6% isolated embryos), probably due to a less efficient washing after cocultivation. Thus, the elimination of bacterial contamination should be improved, applying the bactericides by means of vacuum infiltration, using more efficient bactericides or acidifying the medium for a short time, as some authors suggest (Hammerschlag et al 1997). In conclusion, clusters should be considered the explants of choice, as they present the highest transformation efficiency and are easier to collect and manipulate than isolated embryos.…”
Section: Discussionmentioning
confidence: 99%
“…The higher quantity of proliferating cells per explant probably increased the transformation efficiency; however, bacterial overgrowth increased as well (52.1% clusters contaminated compared with 11.6% isolated embryos), probably due to a less efficient washing after cocultivation. Thus, the elimination of bacterial contamination should be improved, applying the bactericides by means of vacuum infiltration, using more efficient bactericides or acidifying the medium for a short time, as some authors suggest (Hammerschlag et al 1997). In conclusion, clusters should be considered the explants of choice, as they present the highest transformation efficiency and are easier to collect and manipulate than isolated embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Timentin has been used without affecting regeneration with tobacco (Nauerby et al 1997) and tomato (Costa et al 2000). It has been demonstrated that carbenicillin breaks down to give physiologically active levels of the auxin phenylacetic acid, which could explain the positive effect that this antibiotic has on organogenesis of different species (Nakano and Mii 1993;Hammerschlag et al 1997;Yu et al 2001). This breakdown could have produced an excessive auxin concentration in apricot cells, since we have observed that increases in NAA concentration reduced and delayed regeneration from apricot leaves (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In more recent research caulogenesis was facilitated by CARB when the shoots were regenerated indirectly from callus (Suzuki et al 1998;Bhau and Wakhlu 2001;Tang et al 2004). Positive results have also been reported for direct regeneration protocols when an initial dark culture period, that would be expected to stimulate callusing prior to the onset of shoot differentiation, was included (Billings et al 1997;Hammerschlag et al 1997;Dai and Castillo 2007).…”
Section: Shoot Morphogenesismentioning
confidence: 93%
“…Because of their low levels of plant toxicity, b-lactams; particularly CEF, CARB, and timentin, are widely used for Agrobacterium elimination in plant transformation (Hammerschlag et al 1997;Tang et al 2004). Traditionally, cost and antibiotic potency have been among the primary criteria used to select among different b-lactams.…”
Section: Potential Plant Biotechnology Applicationsmentioning
confidence: 99%